Climatic patterns modulate ecosystem and soil respiration responses to fertilization in an alpine meadow on the Tibetan Plateau, China. Issue 1 (12th November 2014) - Jiang, Jing; Shi, Peili; Zong, Ning; Fu, Gang; Shen, Zhenxi; Zhang, Xianzhou; Song, Minghua
Abstract: The responses of ecosystem ( R ec ) and soil ( R s ) respiration to nutrient enrichment have been extensively investigated, aiding our understanding of ecosystem and soil carbon (C) balances in light of global changes. However, the effects of climatic variables and plant growth on CO2 fluxes under nutrient enrichment remain poorly known. We measured aboveground biomass ( Ab ), R ec, and R s during three consecutive growing seasons (2010–2012) in a Tibetan alpine meadow where a nitrogen (N) and phosphorous (P) fertilization experiment began in 2008. The five treatments were Ctrl (no N or P fertilization), LN and HN (addition of 5 and 10 g N m −2 year −1, respectively), LN + P and HN + P (the respective N treatments with 5 g P m −2 year −1 added). LN and HN did not affect R ec, R s, or Ab during the three growing seasons, but both N + P treatments increased Ab in all 3 years. However, the effects of N + P on R ec and R s varied among years: N + P increased R ec and R s at most sampling times in 2010 and 2011, but the effect seemed to reach saturation in 2012. Additionally, R ec and R s were positively correlated with Ab in N + P, indicating that enhanced Ab contributed considerably to the observed variation in R ec and R s . Different climate patterns during three seasons drove the inconsistent relationships of CO2 fluxes with soil temperature and moisture. Our results suggest that temperature and precipitation patterns throughout the growing season are important modulators of CO2 fluxes under increasing nutrient levels in arid alpine meadow ecosystems.